Bispos autóctones em contexto do colonialismo português: questão de soberania política e de autonomia eclesial (1962-1970) - Pereira, João Francisco (Lusitania sacra, 2025)
Diplomatic relations between Portugal and the Holy See during the 1960s were marked by several events. The prolonged exile of D. António Ferreira Gomes, the Second Vatican Council and the visit of Pope Paul VI to Fátima are some of the best known examples. Even so, a substantial part of the documentation present in the Diplomatic Historical Archive on these relations shows that the Ultramar issue was a topic that absorbed much of the attention in the relationship between the two states. It is in this context that, discreetly but with some insistence, the question of appointing black bishops to Portuguese dioceses in Ultramar territories will be raised. Since the conciliar period, the Holy See has pressured the Portuguese government to accept the appointment of indigenous bishops. The government resisted, considering that this would mean the creation of unwanted local leadership, especially in times of war. This research note aims to show the arguments made by both parties for almost a decade that ended with the appointment of a black auxiliary bishop for the diocese of Luanda.